A serotonergic circuit regulates aversive associative learning under mitochondrial stress in C. elegans - Chiang, Yueh-Chen; Liao, Chien-Po; Pan, Chun-Liang (Proceedings of the National Academy of Sciences - PNAS, 2022)
Physiological stress profoundly alters the internal states of the animals and could drive aversive learning, but signaling and circuit mechanisms underlying such behavioral plasticity remain incompletely understood. Here, we show that mitochondrial disruption in nonneural tissues of Caenorhabditis elegans induces learned aversion for nutritious bacterial food that displays features of long-term associative memory. Serotonin secreted from the modulatory NSM neuron acts through the SER-4 receptor in the RIB interneuron to drive bacterial avoidance, with NSM and RIB required for the establishment and retrieval for learned aversion, respectively. NSM serotonin synthesis increases early in the induction of systemic mitochondrial stress. Calcium imaging reveals altered RIB responses to bacterial cues in a fraction of stress-primed but not naïve animals. These findings uncover cellular circuits and neuromodulation that enable aversive learning under stress, and lay the foundation for future exploration of behavioral plasticity governed by internal state changes.